A Study of Vocabulary Learning Strategies Used by Students at Grade XI - Putri Nuraini; Anjar Kusuma Dewi; Andi Patmasari; Nur Sehang Thamrin (LPPM Universitas Advent Indonesia, 2026)
This study aims to find out the vocabulary learning strategies used by students at MAN Insan Cendekia Kota Palu. This research used a survey design by using questionnaire of vocabulary learning strategies (VLS) adopted from Yeh and Wang (2004). The instrument contains 50 items with five categories of vocabulary learning strategies based on Schmitt’s (1990) taxonomy. The population of this research was eleventh grade students. The sample was taken using a convenience sampling technique with a total of 90 students. To calculate total sample from population using Slovin’s formula. The data analysis showed that students used all of the six learning categories of Schmitt strategies; determination strategies, social strategies, memory strategies, cognitive strategies, and metacognitive strategies. But for the most frequently used strategies are determination strategies with mean score is 3.45 and the least frequently used strategies are cognitive strategies with mean score 2.72.